Successful Camouflage Orthodontic Treatment of Class II Malocclusion with Maxillary Severe Crowding: A Case Report - Leni Paramita Nurmalini; Debrinna Rezaumami; Avi Laviana (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2025)
There are some limitations of conventional orthodontic treatment in class II skeletal malocclusion. Ideally, skeletal malocclusion needs surgical orthodontic treatment, but mild to moderate class II skeletal malocclusion can be treated with camouflage orthodontic treatment. This report aims to present that the goal of camouflage treatment of skeletal class II is to disguise the unacceptable skeletal relationship by orthodontically moving teeth, such as extraction of upper premolars followed by anterior retraction. Confidence issues brought a 19-year-old female to RSGM Universitas Padjadjaran. She exhibits skeletal malocclusion symptoms such as a convex facial profile, SNA: 84°, SNB: 78° with ANB: 6°, moderate crowding in the mandibular arch, palatoversion and rotation of the second premolars, a deep overbite (5 mm), a large overjet (5,5 mm), and a shifted midline in the maxillary and mandibular, measuring 2 mm and 1.5 mm, respectively. The first course of therapy was removing the lower left second premolar and the upper two-second premolars—a prescription for braces with MBT 0.022 inch pre-adjustments. Anchorage was strengthened by placing TPA in the maxillary arch. Treatment was finished in 22 months. This case report presents the successful management of camouflage orthodontic treatment of class II skeletal malocclusion by extracting maxillary premolars and unilateral extraction of mandibular premolars to create space and relieve crowding teeth. This treatment was able to change the overbite, overjet, and convexity of the patient's profile to normal. The patient was delighted with the treatment results because she had more confidence when smiling.